NILAI-NILAI PENDIDIKAN MULTIKULTURAL DALAM PIAGAM MADINAH - M. As’ad Nahdly; Ahmad Amiq Fahman (Institut Keislaman Abdullah Faqih Gresik, 2022)
Abstract: The purpose of this study is to see the reality of plurality in Medina, thanks to the constitution of the Medina Charter that can be regulated and managed properly by the Prophet Muhammad. Therefore, how can the values ??contained in the Medina Charter be implemented and integrated into national education. The focus of this research is on how the values ??of multicultural education are viewed from the Medina Charter in national education and the values ??of multicultural education are implemented in national education from the perspective of the Medina Charter. The researcher chose the library research method. Where researchers collect information from available materials in the form of books, archives, journals and other documents that support research. There are two sources of information in library research, namely primary and secondary sources of information. When analyzed, its validity is tested using inductive, deductive, comparative, and interpretive techniques. The results of the study of the Medina Charter have three values ??of multicultural education, namely democracy, respect for human rights and pluralism. In the application of these values ??in national education in the form of democratization of education, humanistic education, and pluralism Keyword: Educational Values, Multicultural Education, Medina Charter